1994
DOI: 10.1002/pd.1970141004
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of amniocentesis between 11 and 15 weeks: Comparison to later amniocentesis controls

Abstract: We studied 693 consecutive early amniocenteses (prior to 15 weeks) and found a spontaneous abortion rate to 28 weeks' gestation of 1.5 per cent. A control group of women having standard amniocentesis (15-20 weeks) experienced a 0.6 per cent fetal loss in the same period. There were no other apparent differences between the two groups. Early amniocentesis results are generally available 4-6 weeks before standard amniocentesis and 1-3 weeks after chorionic villus sampling (CVS). Alpha-fetoprotein (AFP) can be ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 12 publications
(4 reference statements)
2
18
1
2
Order By: Relevance
“…An increased culture failure rate in 'early' amniotic fluids compared with those obtained later in pregnancy has been reported by several authors (Cederholm and Axelsson, 1997;Daniel et al, 1998;Kennerknecht et al, 1992;Nicolaides et al, 1996) while others have reported no difference (Fatemi et al, 1988;Crandall et al, 1994;Eiben et al, 1997). It is difficult to compare these studies with CEMAT because in some a relatively small proportion of fluids was obtained earlier than 13 weeks' gestation and in other cases the total number of fluids cultured was relatively small.…”
Section: Culture Failurecontrasting
confidence: 39%
“…An increased culture failure rate in 'early' amniotic fluids compared with those obtained later in pregnancy has been reported by several authors (Cederholm and Axelsson, 1997;Daniel et al, 1998;Kennerknecht et al, 1992;Nicolaides et al, 1996) while others have reported no difference (Fatemi et al, 1988;Crandall et al, 1994;Eiben et al, 1997). It is difficult to compare these studies with CEMAT because in some a relatively small proportion of fluids was obtained earlier than 13 weeks' gestation and in other cases the total number of fluids cultured was relatively small.…”
Section: Culture Failurecontrasting
confidence: 39%
“…Crandall et al [12] found no significant difference in congenital malformations detected at birth in patients having amniocentesis at less than 15 weeks compared to the controls at 15-20 weeks. The incidence of anomalies was 1.8 and 2.2%, respectively.…”
Section: Early Amniocentesismentioning
confidence: 99%
“…The abortion rate up to week 28 of gestation found after first trimester CVS ranges between 5.6% [13], 4.9% [14], 3.4% [15] and 2.9% [16]. The EAC abortion rates in our study of 2.82% for week 11-12 up to week 28 and 1.82% for week 13-14 up to week 28 are lower or in the same range as the data reported from normal pregnancies without an invasive procedure or after CVS.…”
Section: On the Complication Risk Of Early Amniocentesis Versus Standmentioning
confidence: 99%